Pengaruh Komunikasi Yang Efektif Dan Motivasi Terhadap Kinerja Pegawai Pada Dinas Perhubungan Kabupaten Karo - Sembiring, Menanti (JURNAL AGRICA, 2017)
This research is aim to review the influence of effective communication and motivation towards employee performance at Transportation Department Karo District. The sum of population of this research is about 46 people and all of them is created as sample or total sample. To test the hypothesis which is submitted can be done by partial testing, simultaneous testing and coefficient of determination.The result of this research shows that in partial way, the variable of effective communication and motivation is significantly influence the perfomance employee at Transportation Department Karo district, where tcalculated value in variable of communication is 2,253 and tcalculated value in variable of movation is 4,359, wherever the value of t table is 1,679. By simulataneous testing way, Fcalculated is obtained with 19,582 and the value of Ftable is 3,204. It can be concluded that by simultaneous testing way, variable of effective communication and motivation is significantly influence the employee performance too at Transportation Department Karo district. The result of multiple linier regression  is obtained by the equation y = 8,638 + 0,246x1 + 0,521x2 + e.The value of coefficient of determination stated that 0,477 or 47,70 % of employee performance in Transportation Department Karo district is influenced by effective communication and motivation and the rest 52,30 % is influenced by another factor which is not conducted on this research.